Development of Pop-Up Book Media Based on Contextual Content of Science Learning Material on Animal Life Cycle In Elementary School - Shofi Regitha Azzahra; Mimin Ninawati (Eduvest - Journal of Universal Studies, 2024)
This study focuses on the development and feasibility testing of contextual-based visual pop-up book media for teaching science, specifically the animal life cycle material, in grade IV at SDN Dukuh 08 Pagi. The pop-up book media is designed to address the lack of student understanding of the material delivered through conventional teaching methods. The research method used is Research and Development (RnD) with the 4D development model (Define, Design, Develop, Disseminate). Validation results from media experts show a feasibility percentage of 99%, and validation from subject matter experts shows a percentage of 98%. The implementation of this media in both small and large groups indicates that the pop-up book is highly suitable for use in teaching, with positive responses from students. This media is expected to enhance student creativity and motivation, as well as contribute to the development of more engaging and effective learning media.